La dolce vita. Juliet of the spirits - Rota, Nino, 1911-1979 (Academic Video Online, 2015)
8½, La Dolce Vita, Cinema Paradiso -- these classics of Italian cinema are beloved not only for their storytelling, but also for their unmistakable music. And when that gorgeous music is performed by the Philharmonic and soloists Josh Groban, Joshua Bell, and Renée Fleming -- accompanied by animated graphics and film clips -- it truly becomes an evening in cinema paradise.